EFFECTIVENESS OF WHATSAPP AS A HEALTH PROMOTION MEDIA IN IMPROVING TOOTH BRUSHING BEHAVIOR BASED ON FEDERATION DENTAIRE INTERNATIONALE - Safa’at Bintang Ramadhan; R. Harry Dharmawan Setyawardhana; Galuh Dwinta Sari (Universitas Lambung Mangkurat, 2023)
ABSTRACTBackground: The majority of tooth decay is caused by improper brushing behavior. The correct behavior for tooth brushing refers to the Federation Dentaire Internationale (FDI), including the behaviour of tooth brushing every day at least twice a day, after breakfast and before going to bed at night. The results of RISKESDAS in 2018 reported that only 4.96% of adolescents aged 10-14 years who brushed their teeth properly in the city of Banjarbaru. WhatsApp groups as a media for health promotion is considered as an effective strategy to disseminate information to improve one's knowledge and behavior towards a better outcome. Purpose: To analyze the effectiveness of WhatsApp as a health promotion medium in improving the behavior of brushing teeth properly based on the Federation Dentaire Internationale (FDI) in grade VII students at SMPN 2 Banjarbaru. Material and Methods: This study used a pre-experiment design with one group post test pre test design with simple random sampling technique. The research was conducted at SMPN 2 Banjarbaru with a sample of 173 respondents. Results: The results of the pre test measurement showed that there no respondents in the bad behavior category (0%), 45 respondents (26%) in the moderate category and 128 respondents (74%) in the good category. The result of post test measurement revealed that there were no respondent in bad and moderate category that 173 respondents were fell into good behaviour category. The results of the Wilcoxon comparison test obtained a significance value of 0.000 <0.05, meaning that there was a difference in behavior between before and after being given health promotion. Conclusion: Counseling using WhatsApp social media is effective in increasing the behavior of proper toot brushing according to FDI.Keywords: Health promotion, Proper brushing behavior, Whatsapp